Directive Speech Analysis in Acts 99,99 Komik Strip Kids Jaman Now - Meily Winie Manik (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2022)
This research discuss about the types of directive speech acts in 99,99Komik Strip Kids Jaman Now comic book. This comic book tells about the children daily life with nine ethnics and local wisdom in three languages. The languages are Bahasa, English and local language. The objectives of the study were to find out the types of directive speech acts and to show the most dominant type used in the comic book. This research used Searle and Yule theory to conduct the types of speech acts. There are 4 types of speech act as the focus of this research. They are command, order, request and suggestion. The method of this research is qualitative research. The data was taken from characters utterances on Melayu Deli ethnic and Batak Toba ethnic story. The result of research found 28 directive speech acts. It consists of 6 commands, 1 order, 10 requests and 11 suggestions. The typemost commonly used in thestory is suggestion.